Expanded Mobius Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
An infant born with Mobius syndrome died at 22 days and was found at autopsy to have more widespread involvement of brainstem and cranial nerve nuclei than usual, resulting in an "expanded Mobius syndrome," as reported from the University of Iowa Hospital, Iowa City, IA.